Drug Solubility Enhancement through the Preparation of Multicomponent Organic Materials: Eutectics of Lovastatin with Carboxylic Acids - Andrea Mariela Araya-Sibaja; José Roberto Vega-Baudrit; Teodolito Guillén-Girón; Mirtha Navarro-Hoyos; Silvia Lucia Cuffini (MDPI AG, 2019)
Lovastatin (LOV) is a drug used to treat hypercholesterolemia. Recent studies have identified its antioxidant effects and potential use in the treatment of some types of cancer. However, the low bioavailability related to its poor water solubility limits its use in solid oral dosage forms. Therefore, to improve the solubility of LOV three eutectic systems of LOV with the carboxylic acids benzoic (BEN), salicylic (SAL) and cinnamic (CIN) were obtained. Both binary phase and Tammann diagrams were constructed using differential scanning calorimetry (DSC) data of mixtures prepared from 0.1 to 1.0 molar ratios. Binary mixtures and eutectics were prepared by liquid-assisted grinding. The eutectics were further characterized by DSC and powder X-ray diffraction (PXRD), Fourier-transform infrared spectroscopy (FT-IR) and scanning electron microscopy (SEM). The LOV-BEN, LOV-SAL and LOV-CIN system formed a eutectic at an LOV mole fraction of 0.19, 0.60 and 0.14, respectively. The systems exhibited improvements in LOV solubility, becoming more soluble by five-fold in the LOV-SAL system and approximately four-fold in the other two systems. Considering that the solubility enhancements and the carboxylic acids used are generally recognized as safe by the U.S. Food and Drug Administration (FDA), the LOV eutectic systems are promising materials to be used in a solubility enhancement strategy for pharmaceutical product formulation.